A Confucian Defense of Shame: Morality, Self-Cultivation, and the Dangers of Shamelessness - Berkson, Mark (Religions, 2021)
Many philosophers and scholars in the West have a negative view of shame. In much of post-classical Western ethical thought, shame is compared negatively with guilt, as shame is associated with the “outer”, how one appears before others (and thus is merely a matter of “face”), and guilt is associated with the “inner” realm of the conscience and soul. Anthropologists and philosophers have used this framework to distinguish more morally evolved Western “guilt cultures” from Asian “shame cultures”. Many psychologists also have a negative view of shame, seeing it as damaging to the self and “devastating in its consequences”. In this paper, I argue that the understandings of shame found in these philosophers and psychologists are misguided, and that their flaws can be revealed by looking at the understanding of shame in the classical Confucian tradition. In response to philosophers who see shame as a “lesser” moral emotion than guilt, Confucius (孔子 Kongzi) and Mencius (孟子 Mengzi) will articulate an understanding of shame that has a deeply internal dimension and is more essential in the process of moral cultivation than guilt. In response to the psychologists who warn about the harm of shame, the Confucians will help us distinguish between moral and pathological shame, showing us why the latter is harmful, but the former is something that no moral person can be without. I will show that the Confucian perspective on shame and guilt is profoundly relevant to the historical moment we are living in (particularly the years of the Trump Administration), and that the Confucian view demonstrates that there is something much worse, and far more devastating, than shame in its consequences—shamelessness.